Flash joining of conductive ceramics in a few seconds by flash spark plasma sintering. Issue 15 (December 2019) - Biesuz, Mattia; Saunders, Theo G.; Grasso, Salvatore; Speranza, Giorgio; Sorarù, Gian D.; Campostrini, Renzo; Sglavo, Vincenzo M.; Reece, Michael J.
Abstract: The feasibility of flash joining conductive ceramics using spark plasma sintering is demonstrated. It is shown that graphite disks can be joined in a few seconds (6–10 s electric discharge time) using a SiOC precursor (methyl silicone resin) as an interlayer. Differently from usual flash experiments, the process does not require any pre-heating, allowing a dramatic reduction of the processing time. XPS analysis of the joint revealed a clear evolution of the chemical environment of silicon with a progressive transition from SiOC to SiO2 /SiC. Mechanical tests were performed to determine the fracture toughness (1.0 ± 0.2 MPa m 0.5 ) and fracture energy (40.6 ± 9.8 J/m 2 ) of the interface Flash joining can be applied beyond graphite joining, and opens a novel and flexible processing route for many conductive ceramics, as demonstrate by preliminary work on Kanthal® Super MoSi2 and Cf -reinforced SiC.